The issue of penalties and its execution mode: An empirical study on human rights education - Guimarães, Ana Paula (2021)
As Law teachers at Portucalense University, it has been our objective to research the position of our students with regard to human rights and, in particular, on criminal penalties, their forms of execution and security. We previously conducted a first survey addressed to undergraduate students and, for this work, we conducted an identical survey on Brazilian students who attended the teaching part of the master's degree in Legal and Political Sciences specialization, at our University. These students were presently in Portugal. We intend to understand their position on the theme based on their reality experienced in Brazil. The surveys were answered in the classroom, anonymously and freely. The students already have professional experience in the area of legal sciences, varying their ages between 30/40 years. The results of this empirical study showed respondents’ sensitivity in human rights matters. Prevention, as an end to sentences, was unanimous. Almost everyone said they felt insecure in their country and most of them had also been victims of crime in their country. The majority of students are in favour of the resocialization of the prisoner imposed by the State. However, in relation to the remaining questions, the answers were diversified. This diversity is explained by motivations of a security nature given the extension of the criminal phenomenon in Brazil.